2016
DOI: 10.4172/2161-1009.1000285
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Selected Rice (Oryza Sativa L.) Genotypes Based on Gel Consistency and Alkali Digestion

Abstract: Quality assessment of rice genotypes involves physicochemical and sensory test. A physicochemical test relies on the rice chemical composition, cooking quality, gelatinization temperature and physical properties of cooked rice. The aim of this study was to determine the physicochemical characteristics of selected Kenyan and Tanzanian genotypes based on gel consistency and alkali digestion. Diverse classes of rice exist with different expression levels of gel consistency and alkali digestion. As these traits ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…After germination, the gel consistency of rice ranged from 60.67 to 112.33 mm which showed that all germinated rice varieties had soft gel consistency. The soft and hard gel consistency values are accounted by the biallelic variability at the waxy locus (Chemutai et al, 2016). The gel consistency is expressed by the flowing distance.…”
Section: Resultsmentioning
confidence: 99%
“…After germination, the gel consistency of rice ranged from 60.67 to 112.33 mm which showed that all germinated rice varieties had soft gel consistency. The soft and hard gel consistency values are accounted by the biallelic variability at the waxy locus (Chemutai et al, 2016). The gel consistency is expressed by the flowing distance.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment also, PC2 showed an opposite relationship between gel consistency and apparent amylose content. Chemutai, Musyoki, and Kioko [ 27 ] explained gel consistency as the indirect method used in screening cooked rice for its hardness when cooked. Hard gel consistency is due to formation of rigid rice gels; as a result, association of starch polymers in the aqueous phase and intermediate gel consistency is due to the effects of minor genes, for instance gene interaction between waxy pullulanase or waxy and BEIII genes.…”
Section: Discussionmentioning
confidence: 99%
“…Steps for the determination of GT were followed by the method reported by Chemutai et al [21]. Briefly, 10 polished rice kernels were set in a Petri dish containing 10 mL of potassium hydroxide (KOH) 1.7% (w/v) which was prepared freshly.…”
Section: Determination Of Gelatinization Temperature (Gt)mentioning
confidence: 99%